2012
DOI: 10.1590/s0004-27302012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visceral and subcutaneous fat in bone mineral density of obese adolescents

Abstract: Objective: To verify the influence of visceral and subcutaneous fat, as well adipokines in bone mineral density (BMD) in obese adolescents. Subjects and methods: The study involved 125 postpubertal obese adolescents (45 boys and 80 girls). Anthropometric measurements, body composition, visceral and subcutaneous fat, and BMD were determined. Leptin, adiponectin, and insulin levels also analyzed. Results: Data demonstrated a negative relationship between BMD with insulin resistance, visceral fat and leptin conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
14

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
2
17
0
14
Order By: Relevance
“…VAT was found to be a negative predictor of bone mass. Another study, with adolescent girls, supported the negative effect of visceral fat on BMD (86). In Korean healthy men and women, it was found that visceral fat, measured by computed tomography, was independently and negatively associated with bone mass (87).…”
Section: Bone and Energy Metabolismmentioning
confidence: 88%
“…VAT was found to be a negative predictor of bone mass. Another study, with adolescent girls, supported the negative effect of visceral fat on BMD (86). In Korean healthy men and women, it was found that visceral fat, measured by computed tomography, was independently and negatively associated with bone mass (87).…”
Section: Bone and Energy Metabolismmentioning
confidence: 88%
“…Corroborando estes dados, a literatura identifica que a gordura intra-abdominal é inversamente relacionada com a DMO (8) . Essa relação inversa baseia-se na presença citosinas pró-inflamatórias produzidas na região central do tecido adiposo, quem possam estar inibindo a potencialização do crescimento ósseo em jovens obesos (22) . Outro fator que deve ser levado em consideração refere-se ao fato de a insulina estar relacionada negativamente com o acumulo de gordura, principalmente intra-visceral.…”
Section: Discussionunclassified
“…Body composition appears to interfere with 25(OH) D synthesis and metabolism hence obese individuals tend to have lower serum concentrations than the non-obese population (26). Campos et al (26) assessed the influence of visceral and subcutaneous fat on bone mineral density (BMD) in post-pubescent adolescents, and found that visceral fat has a negative effect on bone mass, while the subcutaneous kind has a positive impact only on boys, and suggest that these opposing forms of interaction of adipose tissue on bone mass occur because of the differences in the expression and secretion of the adipokines.…”
Section: Vitamin D Deficiency and Obesitymentioning
confidence: 99%